EXAMINING THE PROMOTION MIX STRATEGY IN THE TOURISM AREA LIFE CYCLE (TALC) STAGE OF TETEBATU TOURISM VILLAGE - Lalu Rizaldi Wisnu Wardhana (Bajang Institute, 2025)
This research discusses promotional mix strategies in Tetebatu Village, Sikur District, East Lombok Regency in phasing the position of village development through theory. Tourism Area Life Cycle (TALC). This research is based on the success of Tetebatu Village in representing Indonesia in the 2021 Best Tourism Villages event held by the United Nations World Tourism Organization (UNWTO), which ultimately gave rise to the perception among the community that this success was inseparable from the participation of the Tetebatu Village Government in it. Apart from this success, Tetebatu Village also has very high historical value in its tourism development because it is the pioneer of the first tourist village in NTB as evidenced by the existence of Wisma Soedjono which has existed since the Dutch East Indies colonial era. This type of research uses qualitative research methods. Data collection methods in this research used observation, interviews and documentation. Researchers record all data obtained in the field and then sort the data needed. Based on the findings and analysis carried out by researchers, it shows that the development of the Tetebatu Tourism Village is a tourist village that applies the concept of sustainable tourism by maximizing the role of existing community institutions such as the Tetebatu Tourism Village Management Agency, Pokdarwis, Tourism Actors and the Community who are directly involved in it. The results of further research are that the Tetebatu Tourism Village Government implements four of the five components of the promotional mix (promotion mix) which includes advertising (advertising), sales promotion (sales promotion), public relations (public relations), and direct marketing (direct marketing) as well as the results of the related analysis, namely that Tetebatu Village is in the development phase/stage (development) based on TALC theory (Tourism Area Life Cycle).